เครือข่ายการสื่อสารกลุ่มและบทบาทในการอนุรักษ์เพลงสุนทราภรณ์ของกลุ่มอนุรักษ์เพลงและลีลาศสุนทราภรณ์ - ตติยา เลาหตีรานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
Objective of this research is to study the Communication Network of the Suntaraporn s Songs and Dance Conservation Group characteristic and the role of this group and the persons involved. This qualitative research was studied via two approaches : In-depth interview and Non-participant observation. Conclusion from this research : Group objection is to be the member meeting center for Suntaraporn s song conservation activities. The group communication network characteristic can be classified into 4 levels as follow : 1. The Leader Group has combined activities of "Wheel Network" and "All-channel Network" 2. The communication between Leader Group and members is "Wheel Network" 3. The communication among members is "Circle Network" 4. The communication between the Conserved Group and the others has 2 form : "Wheel Network and Radial Network" Roles of the Conservation Groups can be classifies into 3 main categories : 1. Conserved Group and the Leader are the center for people who admire Suntaraporn and perform all the conservation activities. 2. The membership Group supports the above activities and distribute to their close persons. 3. Non-membership group can be classified into 2 subgroups : 1.) Involving in the Suntaraporn Band Show, rerecord and distribute Suntaraporn s work. 2.) others who admire Suntaraporn support Suntaraporn s song and work by chances.